PEMETAAN DIGITAL FAKULTAS TEKNIK UNIVERSITAS TADULAKO BERBASIS GEOGRAPHIC INFORMATION SYSTEM (GIS) - Nugraha, Deny Wiria; Dodu, A.Y Erwin; Makbul, Mohammad (ScientiCO : Computer Science and Informatics Journal, 2019)
Tadulako University is the largest tertiary institution in Central Sulawesi and every year new students are registered to Tadulako University comes from inside and outside Central Sulawesi Province. Prospective students from various regions certainly many are looking for information on the campus area, especially in the Faculty of Engineering, the University of Tadulako through existing media. Seeing this, the authors conducted a research aiming to make a digital mapping of the Tadulako University Faculty of Engineering based on the Geographic Information System (GIS) application using the website, and at the same time giving directions to the location of the room using 360-degree photos and how to utilize the Tadulako University Faculty of Engineering Mapping for determine the location on the website. The method used is to use Geographic Information Systems (GIS) and the results of the study that the author found is using the HyperText Preprocessor (PHP) programming language and JavaScript and retrieve data from 360 degrees as many as 245 photo locations in each Department of Engineering at the University of Tadulako with 1-time taking photos requires 40 times the taking of 360-degree objects with a distance between one room with another so that it connects the existing mapping at the Department of Engineering, Tadulako University using the website.Â